2020
DOI: 10.1371/journal.pntd.0008334
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite epidemiology and health-seeking behavior in Akonolinga health district, Cameroon: Cross-sectional study

Abstract: Background Snakebite envenoming causes 81,000-138,000 annual human deaths and pain, terror, or disability in 4.5-5.4 million victims. Accurate community-based epidemiological data is scarce. Our objective was to assess snakebite incidence, mortality, and health-seeking behavior, in an affected health district of Cameroon. Methods We conducted a cross-sectional multicluster household survey in Akonolinga health district, Centre Region, Cameroon, from October to December 2016. Using probability-proportionalto-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 22 publications
(32 reference statements)
4
28
3
1
Order By: Relevance
“…The Ministry of Health in Brazil has been distributing around 230,000 ampoules of antivenom to approximately 2000 hospitals free of charge annually [16], which is likely one of the reasons for the low mortality rates associated with snakebites in Brazil found in this and prior studies [9,16,[28][29][30]41]. Brazil's case-fatality rate for snakebites of around 0.4%, found in our study and the previous study by Bochner [9], is particularly low if compared with studies in other countries, such as the reported case-fatality rate of 3% in a recent district-level study in Cameroon [42], and an estimated case-fatality rate of 3.2% for in-hospital cases of snakebite envenoming in India [43]. According to Chippaux [44], the model that exists in Brazil regarding antivenom distribution, as well as existing infrastructure that ensures treatment for many people, is a good model for other low-and middle-income countries, including those in Africa and Asia.…”
Section: Discussioncontrasting
confidence: 50%
“…The Ministry of Health in Brazil has been distributing around 230,000 ampoules of antivenom to approximately 2000 hospitals free of charge annually [16], which is likely one of the reasons for the low mortality rates associated with snakebites in Brazil found in this and prior studies [9,16,[28][29][30]41]. Brazil's case-fatality rate for snakebites of around 0.4%, found in our study and the previous study by Bochner [9], is particularly low if compared with studies in other countries, such as the reported case-fatality rate of 3% in a recent district-level study in Cameroon [42], and an estimated case-fatality rate of 3.2% for in-hospital cases of snakebite envenoming in India [43]. According to Chippaux [44], the model that exists in Brazil regarding antivenom distribution, as well as existing infrastructure that ensures treatment for many people, is a good model for other low-and middle-income countries, including those in Africa and Asia.…”
Section: Discussioncontrasting
confidence: 50%
“…Depressive symptoms and post-traumatic stress disorder are the most common psychological conditions reported following snakebite ( Khosrojerdi and Amini, 2013 ; Williams et al, 2011 ). Non-specific somatic manifestations of psychological problems resulting from the experience of snakebite, which may be related to socio-cultural beliefs that promote a sick role are also described in the literature (Rodríguez and Gutiérrez, 2019; Alcoba et al, 2020 ).…”
Section: Resultsmentioning
confidence: 95%
“…This study collected data about who delivered the engagement to the communities; no publications mentioned the involvement of traditional healers, yet the key role that they play in the traditional management of SBE in many communities is well known ( Alcoba et al, 2020 ; Sloan et al, 2007 ). Although it can be challenging and time-consuming, the NTD community must seek ways to work with traditional healers and community and religious leaders, who hold trusted and influential positions within their communities and thus are key in driving behavioural change ( Awah et al, 2018 ; Kadam et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%